Monetary transmission mechanism in Central and Eastern Europe: gliding on a wind of change - Fabrizio Coricelli; Balázs Égert; Ronald MacDonald (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
This paper surveys recent advances in empirical studies of the monetary transmission mechanism (MTM), with special attention to Central and Eastern Europe.In particular, while laying out the functioning of the separate channels in the MTM, it explores possible interrelations between different channels and their impact on prices and the real economy.The empirical findings for Central and Eastern Europe are then briefly compared with results for industrialized countries, especially for the euro area.We highlight potential pitfalls in the literature and assess the relative importance, and potential development, of the different channels, emphasizing the relevant asymmetries between Central and Eastern European countries and the euro area.
URN:NBN:fi:bof-201408072128
Keywords: E31; E51; E58; F31; O11; P20; 330; Monetary transmission; transition; Central and Eastern Europe; credit channel; interest rate channel; interest-rate pass-through; exchange rate channel; exchange rate pass-through; asset price channel